1996
DOI: 10.1063/1.362857
|View full text |Cite
|
Sign up to set email alerts
|

Voltage enhancement in quantum well solar cells

Abstract: It is known that quantum well solar cells (QWSCs) can enhance short circuit current and power conversion efficiency in comparison with similar, conventional solar cells made from the quantum well (QW) barrier material alone. In this article we report measurements of the dark-current and open-circuit voltage (Voc) of a number of quantum well cells in three different lattice-matched material systems, namely, Al0.35Ga0.65As/GaAs, GaInP/GaAs, and InP/InGaAs. We also present the results obtained from comparable con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 14 publications
3
27
0
Order By: Relevance
“…(1), then the J(V) relation is computed and the V oc and η are determined. Table 1 displays Voc for four QWSCs [8], showing a good agreement between experimental and calculated values. …”
Section: Resultssupporting
confidence: 50%
“…(1), then the J(V) relation is computed and the V oc and η are determined. Table 1 displays Voc for four QWSCs [8], showing a good agreement between experimental and calculated values. …”
Section: Resultssupporting
confidence: 50%
“…Notably, in quantum well cells based on GaInP/ GaAs/Ge three stack layers, there is a concern over the issue of arsenic penetrating into Ge and effectively doping it. 11,12 It should thus be anticipated that As penetration will be an issue in quantum well cells with Si 1−x−y Ge x Sn y buffer layers. Finally, Ge alloys might be suitable for tailoring the properties of self-organized metallic nanostructures which grow on Ge surfaces.…”
mentioning
confidence: 99%
“…Ragay et al have demonstrated fractional efficiency enhancements, under simulated solar illumination (AM 1.5), of up to 7% using In 0.2 Ga 0.8 As/GaAs MQW solar cell [3]. Beside InGaAs/GaAs material system [3][4][5][6], other materials have also been investigated to date such as AlGaAs/GaAs [7], InGaAs/InP [8], InP/InGaAsP [9], and more recently in GaAsP/InGaAs strainbalanced solar cells [10].…”
Section: Introductionmentioning
confidence: 99%